Perbedaan kadar interleukin-6 pada pasien dengan dan tanpa stenosis koroner signifikan - Fatiah dr; Ratna Akbari Ganie; Andre Pasha Ketaren (Fakultas Kedokteran USU, 2017)
Introduction : Coronary heart disease (CHD), characterized by coronary arteries stenosis, is the end result of atherosclerosis. Interleukin-6seems to be the key point in process of atherosclerosis.The aim of this study is to find out whether there is a difference between serum Interleukin-6 level in patients with and without significant coronary stenosis.Methods : A cross-sectional observational analytic study was performedto 34 patients with suspected CHD that underwent coronary angiographyin H.Adam Malik hospital, Medan from February- April 2016.Patients were divided into 2 groups, 17 patients with significant coronarystenosis and 17 patients without significant coronarystenosis.Serum Interleukin-6 level were measured.Results : The medianvalue of serum Interleukin-6 levelin patients with significant coronarystenosis was 14.7 pg/mLand patients without significant coronarystenosis was 12.62pg/mL. There was no significant difference between serum Interleukin-6 level in patients with and without significant coronary stenosis ( p=0.301).Conclusion : There was no significant difference between serum Interleukin-6 level in patients with and without significant coronary stenosis.Keywords : Interleukin-6, Atherosclerosis, CHD